Generalizations of the Optimal Final Inventory Model - Hadley, G. (Management Science, 1962)
The purpose of this note is to generalize the optimal final inventory model presented previously [Hadley, G., T. M. Whitin. 1961. An optimal final inventory model. Management Sci. 7(2) 179–183]. Two generalizations are made. First, the mean demand is allowed to vary with time so that dynamic situations may be studied. Secondly, the date of obsolescence is no longer required to be fixed but is instead allowed to be described by a probability distribution.